Perspektif Kinerja dan Kepuasan Karyawan ditinjau dari Motivasi Kerja dan Disiplin Kerja - Lydia Rossa Marwita; Dian Prawitasari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
Performance is the main benchmark of employee work in a company. Performance describes the level of work productivity of employees as well as to see the extent to which employees can contribute to the company. The purpose of this study is to determine the perspective of performance and satisfaction in terms of Work Motivation and Work Discipline. The sample used was 75 employees of PT Indocipta Wisesa. The results showed that motivation has a positive perspective on job satisfaction while work discipline has a positive perspective on performance